Pengaruh Interaksi Sosial Peserta Didik di SMA/SMK Jawa Timur sebagai Fungsi Lingkungan Pendidikan - Arintia Prasasti Setyo Ningrum; Ainun Tiana; Hilma Farilla; Yuliana Babul Jannah; Firdha Yusmar; I Ketut Mahardika; Rizka Elan Fadilah (Pendidikan Fisika FKIP UNEJ, 2022)
Learners are an input component of the education system and are processed in the educational process so that they can produce quality human resources in accordance with educational goals. Social interaction is a relationship that occurs in the daily life of an individual with many people around him. Social ensures that each student feels included in the group, helps students communicate and learn to get along with others, and respects students with other students and adults. The educational environment is a place where educational activities take place in accordance with socio-cultural conditions and situations. A person cannot be separated from his environment. Meanwhile, education is also very much needed. This means that education cannot be separated from environmental conditions. Therefore education is always related to the environment. The educational environment includes all external conditions and influences on educational activities. Humans have various skills that can be developed through experience. In general, the function of the educational environment is to support students in interacting with different environments (physical, social, and cultural), and in particular with the various educational resources available, to achieve optimal educational goals.